Peran Pembelajaran Berbasis Lingkungan dalam Menumbuhkan Kesadaran Konservasi pada Siswa - Tegar Adinata; Jatmiko Bramantyo Setiawan (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
Environmental-based learning plays a crucial role in fostering students' conservation awareness by integrating real-world experiences into the educational process. This study aims to analyze the effectiveness of environmental-based learning in increasing students' awareness and responsibility toward environmental conservation. A qualitative approach was employed, involving observations, interviews, and document analysis in schools that implement environmental-based learning programs. The findings reveal that hands-on experiences, such as outdoor learning activities and school-based conservation projects, significantly enhance students' ecological awareness and proactive attitudes toward environmental preservation. The implications of this study highlight the importance of integrating environmental education into the curriculum to cultivate a sustainable mindset among students.